2006
DOI: 10.1001/archderm.142.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Dermal Angiomatosis of the Breast

Abstract: Background: Diffuse dermal angiomatosis is rare and usually considered a variant of reactive angioendotheliomatosis. It generally involves the extremities of patients with severe vascular disease and other comorbidities. Two patients with breast involvement have been described; however, neither had a relevant medical history or a vaso-occlusive disorder, but both had large pendulous breasts, and 1 was positive for IgM anticardiolipin and antinuclear antibodies.Observations: A 53-year-old woman had a reticulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 10 publications
(19 reference statements)
1
39
0
5
Order By: Relevance
“…2 Since it was first described in 1994 by Krell et al, 3 only 14 cases have been reported worldwide in the medical literature. 1,2,[4][5][6][7][8][9][10][11][12] The clinical presentation of patients varies, with skin conditions ranging from erythematous to violaceous patches and indurated plaques that may ulcerate; these are usually quite tender. Characteristic histopathologic findings include diffuse extravascular benign endothelial cells throughout the dermis that are both CD31 1 and CD34 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Since it was first described in 1994 by Krell et al, 3 only 14 cases have been reported worldwide in the medical literature. 1,2,[4][5][6][7][8][9][10][11][12] The clinical presentation of patients varies, with skin conditions ranging from erythematous to violaceous patches and indurated plaques that may ulcerate; these are usually quite tender. Characteristic histopathologic findings include diffuse extravascular benign endothelial cells throughout the dermis that are both CD31 1 and CD34 1 .…”
mentioning
confidence: 99%
“…The extremities have been thought to be most commonly involved; however, we identified 5 cases involving the breasts that have been reported. 2,7,8,10,11 We present an additional 5 women with DDA of the breast and review the existing literature.…”
mentioning
confidence: 99%
“…CRA has often been described in association with many different systemic or local diseases such as rheumatoid arthritis, bacterial endocarditis, cryoproteinemia, lymphoproliferative disorders, peripheral atherosclerosis, or an arteriovenous shunt [10,11] (table 1). …”
Section: Discussionmentioning
confidence: 99%
“…Häufig wird zudem ein Nikotinabusus angegeben. Es wurden auch Fälle mit Lokalisation der Hautverän-derungen an der Brust beschrieben, für die lokale Ischämievorgänge infolge physikalischer Belastung der Haut durch eine Makromastie verantwortlich gemacht wurden [3]. In der Mehrzahl der Fälle kommt es zu einer raschen Remission der Hautverände-rungen nach Beseitigung der Ischämie, z.…”
Section: Histologieunclassified
“…Die publizierten Fälle einer diffusen dermalen Angiomatose waren meist an den distalen Extremitäten lokalisiert und standen fast ausschließlich in Verbindung zu arteriovenösen Shunts bzw. arteriosklerotisch stenosierten und okkludierten Gefäßen [3]. Bisher wurde erst 1 Fall einer abdominal lokalisierten DDA beschrieben, bei dem weder arteriosklerotische noch gefäßstenosieren-de lokale Prozesse zugrunde lagen und eine mögliche Assoziation zu lokalen Immunglobulinablagerungen und zu einer monoklonalen Gammopathie gefunden wurde, sodass eine differenzialdiagnostische Abgrenzung zur reaktiven Angioendotheliomatose zu diskutieren wäre [5].…”
Section: Histologieunclassified